2022
DOI: 10.1136/bmjgh-2022-009584
|View full text |Cite
|
Sign up to set email alerts
|

Ensuring quality in contextualised cancer management guidelines for resource-constraint settings: using a systematic approach

Abstract: To address the wide variation in access to cancer care in India requires strengthening of infrastructure, trained oncology workforce, and minimisation of out-of-pocket expenditures. However, even with major investments, it is unlikely to achieve the same level of infrastructure and expertise across the country. Therefore, a resource stratified approach driven by evidence-based and contextualised clinical guidelines is the need of the hour. The National Cancer Grid has been at the forefront of delivery of stand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…19 Another welcome trend in this contemporary medical field, which resonates with our low-cost pathway, is an increased call for ensuring the involvement of all LMIC stakeholders, when framing contextualised guidelines. 20,21 The lack of long-term follow-up is a major limitation of our study as we are not able to calculate recurrence rate, overall and disease-specific survival with the short follow-up allowed by our study. Our sample size is also small but since >70% of patients present with locally advanced breast cancer, EBC patients take much longer to recruit.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…19 Another welcome trend in this contemporary medical field, which resonates with our low-cost pathway, is an increased call for ensuring the involvement of all LMIC stakeholders, when framing contextualised guidelines. 20,21 The lack of long-term follow-up is a major limitation of our study as we are not able to calculate recurrence rate, overall and disease-specific survival with the short follow-up allowed by our study. Our sample size is also small but since >70% of patients present with locally advanced breast cancer, EBC patients take much longer to recruit.…”
Section: Discussionmentioning
confidence: 98%
“…19 Another welcome trend in this contemporary medical field, which resonates with our low-cost pathway, is an increased call for ensuring the involvement of all LMIC stakeholders, when framing contextualised guidelines. 20,21…”
Section: Discussionmentioning
confidence: 99%
“…38 Further, development and/or utilisation and implementation of evidence-based consensus care guidelines, pathways and strategic frameworks for the delivery and strengthening of treatment and care services will be essential in overcoming existing barriers and gaps in cancer control. 39 Comprehensive scoping of necessary data and associated systems, such as cancer registries or mechanism, administrative, supply chain and workforce data, will be essential to ensure that Coalition activities are grounded in evidence and areas of unmet need. It is therefore recommended that future research focus on this issue as a priority.…”
Section: Discussionmentioning
confidence: 99%
“…Studies where the low-value care was identified using a list-based initiative alone, such as Choosing Wisely, were excluded except where there was evidence of contextualisation of the list as the care listed may not be generalisable to all settings or circumstances. Limitations to generalisability may be due to the lack of representation of diverse resources, infrastructure and people at multiple levels of hospital settings in the development of the list 35. We had initially thought that if we detected many non-English studies that would otherwise be eligible, that it would not be possible to translate each of these articles into the English language due to the limited resources we had available to complete this review.…”
Section: Methodsmentioning
confidence: 99%